Improving visual interaction design in e-learning through Realtime Eye Tracking System. - Masood, Mona (Universiti Sains Malaysia, 2017)
This project aims to detect one's visual and cognitive behavior via analyzing his/her eye movement captured through real time eye tracking system. Through detecting a person's eye path and duration on a specific display we have the ability to forecast the person's curiositylinterestldifficulty/confusion at various parts of the display, either with text and/or visuallillustration.